(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Due to the significant benefits in economy of Uzbekistan, the current agriculture businesses have become increasingly advantageous and are supported by local government. Inspired by this, many studies have investigated different aspects of the agricultural sector, especially competitiveness. However, the main characteristics and overall findings of these studies are scattered in term of competitiveness analysis of agricultural market in Uzbekistan, and to the best of our knowledge, there has been no attempt yet to systematically synthesize the literature produced so far on competitiveness in the agricultural market. Thus, this paper presents the results of analyzing and systematically synthesizing the literature that has been explicitly produced on the competitiveness of agricultural sector. We found a growing body of literature on the presence of competitiveness in the agricultural market, where there are indications that the main intentions behind the agricultural market are mostly affected by the following contributive research areas: land use, water management, farm restructuring, clustering in the agro-industrial complex. This implies that the research of competitiveness analysis in agricultural markets is a popular topic in Uzbekistan. In total, a pool of 30 papers published in 12 journals was selected for further analysis by using both automatic and manual search strategies. Our review study supports the relevant communities including researchers and academics, investors, and regulators by providing a structured network analysis for literature strands and the basis for better regulation and protection of investors in the agricultural market to cultivate and manage healthy competition. It also helps pave the way for further research.